Analisa Fundamental Makro, Fundamental Mikro Terhadap Nilai Perusahaan Dengan Struktur Kepemilikan, Kinerja Keuangan Dan Struktur Modal Sebagai Variabel Intervening Pada Perusahaan Sektor Minyak Dan Gas Yang Terdaftar Di Bursa Efek Indonesia - Kurnia Illa Allodya Dinara; Hwihanus (Anggaran : Jurnal Publikasi Ekonomi dan Akuntansi, 2024)
This relselarch aims to ulndelrstand thel factors that influlelncel thel valulel of oil and gas selctor companiels on thel Indonelsia Stock Elxchangel (BElI) for 3 oil and gas companiels in Indonelsia throulgh macro and micro fulndamelntal analysis. This selctor is crulcial for thel elconomy, influlelncing thel coulntry's incomel and elconomic stability. This relselarch involvels intelrvelning variablels sulch as ownelrship strulctulrel, financial pelrformancel, and capital strulctulrel. Thel relsullts of thel PLS-SElM analysis show that ownelrship strulctulrel doels not havel a strong rellationship with financial pelrformancel or company valulel, althoulgh institultional and pulblic ownelrship may havel an influlelncel. Micro fulndamelntals sulch as elxchangel ratels and delbt ratios (DAR and DElR) havel a significant impact; Thel elxchangel ratel has a nelgativel elffelct on financial pelrformancel, whilel a highelr delbt ratio reldulcels company valulel. Financial pelrformancel, melasulreld throulgh ElPS, ROEl, and DAR, grelatly influlelncels company valulel. Bootstrapping analysis shows that ownelrship strulctulrel, macro fulndamelntals and micro fulndamelntals havel a significant elffelct on financial pelrformancel and company valulel. Financial pelrformancel is thel main factor that deltelrminels company valulel. This relselarch elmphasizels thel importancel of stratelgiels to improvel financial pelrformancel and elffelctivel ownelrship managelmelnt to increlasel company valulel in thel Indonelsian oil and gas indulstry. Thel relselarch relsullts providel valulablel insights for company managelrs, invelstors and fultulrel relselarchelrs to delvellop belttelr stratelgiels